SEMANTIC MODELS FOR WEB APPLICATION DESIGN - PIKH, Iryna; MERENYCH, Yulian (Computer systems and information technologies, 2025)
The development of web applications is often carried out within tight deadlines and under limited resources, which complicates adherence to the principles of high-quality design. The design of modern web applications requires consideration of a wide range of criteria that affect usability, accessibility, and the overall effectiveness of user interaction. Given the increasing complexity of digital interfaces, there is a growing need for the development of a theoretically grounded approach to evaluating design quality. The aim of this study is to develop semantic models for formalizing the factors influencing the quality of web application design. The application of formalized models makes it possible to systematize expert knowledge, enhance the objectivity of decision-making, and ensure the reproducibility of results regardless of subjective factors. This article identifies a set of factors that influence the quality of web application design. To achieve this, methods of expert evaluation and semantic modeling are employed. For the quantitative analysis of criterion significance, the rating scale method is applied, and indicators of variation and consistency of expert judgments are calculated. Three main categories of criteria are defined: ergonomics and cognitive principles of interaction; accessibility and inclusivity; and information architecture and visual design. Semantic models representing the relationships between factors within each category are constructed. The proposed approach enables the formalization of expert knowledge and provides a foundation for the further automated evaluation of web application design quality using fuzzy logic methods. The developed semantic models can also be integrated into decision support systems for the design of digital products. Furthermore, they may serve as a basis for the development of educational materials and tools for auditing web application design in accordance with contemporary standards.